Marketing Knowledge Management dan Inovasi Media Digital sebagai Determinan Kinerja UMKM - Ce Gunawan; Galih Raspati (Jurnal Salingka Nagari, 2025)
This study aims to examine the influence of Marketing Knowledge Management (MKM) and Digital Media Innovation on SME Performance within the context of digital economic transformation in Indonesia. The research is motivated by the growing need for digitalization among small and medium enterprises (SMEs), which is often constrained by limited knowledge management capabilities and uneven technological innovation adoption. A quantitative associative approach was employed, utilizing primary data collected through questionnaires from 100 SME owners in West Java Province. Multiple regression analysis was conducted to test the relationships among variables. The results indicate that digital media innovation has a positive and significant effect on SME performance, while MKM does not show a direct significant impact, although it may exert an indirect influence through digital innovation. These findings reinforce the Resource-Based View and Dynamic Capability Theory, emphasizing that knowledge-based and technology-driven innovation constitute key strategic resources for enhancing competitive advantage among SMEs. Theoretically, this research contributes to expanding the understanding of the synergistic relationship between marketing knowledge management and digital innovation in improving business performance. Practically, the study implies that SMEs should strengthen their digital capabilities and integrate knowledge management strategies with digital innovation practices to achieve sustainable growth in a knowledge-driven economy.